2008
DOI: 10.1007/s10820-008-9097-x
|View full text |Cite
|
Sign up to set email alerts
|

Calculations of free energy barriers for local mechanisms of hydrogen diffusion in alanates

Abstract: Brute force histogram calculation and a recently developed method to efficiently reconstruct the free energy profile of complex systems ( the single-sweep method) are combined with ab initio molecular dynamics to study possible local mechanisms for the diffusion of hydrogen in sodium alanates. These compounds may help to understand key properties of solid state hydrogen storage materials. In this work, the identity of a mobile species observed in experiments characterizing the first dissociation reaction of so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
44
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(45 citation statements)
references
References 25 publications
1
44
0
Order By: Relevance
“…It is interesting to see that the activation energy tends to be higher with the increasing of the size of metal cation. The value of CaAlH 5 is much higher than those of K 3 AlH 6 and Na 3 AlH 6 which are technically reversible [8,24], this indicates that mass transport is much more difficult in the dehydrogenation and rehydrogenation processes of CaAlH 5 . Fortunately, FeF 3 -doped sample exhibits favorable value compared to those of doped K 3 AlH 6 and Na 3 AlH 6 .…”
Section: Influence Of Fef 3 Doping On the Dehydrogenation Performancementioning
confidence: 95%
See 1 more Smart Citation
“…It is interesting to see that the activation energy tends to be higher with the increasing of the size of metal cation. The value of CaAlH 5 is much higher than those of K 3 AlH 6 and Na 3 AlH 6 which are technically reversible [8,24], this indicates that mass transport is much more difficult in the dehydrogenation and rehydrogenation processes of CaAlH 5 . Fortunately, FeF 3 -doped sample exhibits favorable value compared to those of doped K 3 AlH 6 and Na 3 AlH 6 .…”
Section: Influence Of Fef 3 Doping On the Dehydrogenation Performancementioning
confidence: 95%
“…As-prepared 120 [24] Doped 97-100 [24] for the as-prepared and FeF 3 -doped samples. It is observed that the activation energy of the as-prepared sample is 153.4 kJ/mol, which is in good agreement with the published result in other literature [15].…”
Section: Influence Of Fef 3 Doping On the Dehydrogenation Performancementioning
confidence: 99%
“…Derivation and details of single sweep method to obtain free energy curves are reported in the seminal works of Vanden-Eijnden, Ciccotti and co-workers [18,19,24]. Here, after describing the system, we briefly summarise the main points of the method and report how we have applied it to our particular case.…”
Section: Methodsmentioning
confidence: 99%
“…For each pK a calculation, we have first performed TAMD [19,24] simulations to span values of the O-H distance and thereby generate initial conditions for the free energy curve reconstruction performed in a second stage. In the TAMD simulation, an extended Lagrangian is used to couple the physical order parameters to an additional fictitious variable, itself having a fictitious mass, by means of a harmonic coupling.…”
Section: Temperature Accelerated Molecular Dynamicsmentioning
confidence: 99%
See 1 more Smart Citation